Peran Guru Sebagai Pendidik dalam Pencegahan Bullying Siswa Di Sekolah Dasar - Firda Khairati Amris; Farida Ariani; Arief Arafat Hankam; Nurva Dillatul Vatin; Joni Indra Wandi (Institut Agama Islam Sumatera Barat, 2024)
The act of bullying is one of the actions that harm others, some of the bullying acts that usually occur in schools include being able to bully mentally and physically. In this bullying, it can be fatal for the victim, if it occurs continuously for a long period of time, a person's psychological condition will deteriorate to the point that the child's future tendencies can be disturbed. In this case, the role of teachers as educators is not only to provide academic instruction to students but also to provide an understanding of psychological education. So that this act of bullying is prevented from the beginning and it is hoped that there will be no more cases of bullying at school. The purpose of this study is to identify the role of teachers in preventing student bullying in elementary schools. The research method carried out is a literature review method to compile an in-depth conceptual framework. The result of the discussion in this article is that there are several factors that cause bullying, namely kelualrgal, sekolalh, falktor sebalyal group, social environmental conditions, television talyalngaln and medial cetalk. And the results of this research show that the main cause of this bullying habit is temperament.